BANK RESOLUTION - Vasile NEMEŞ; Gabriela FIERBINŢEANU (Challenges of the Knowledge Society)
The bank resolution represents one of the technical and legal instruments introduced in the legislative framework belonging to the banking financial market. Within the resolution process, credit institutions and other financial entities, together with supervisory and resolution authorities, are required to develop and implement a series of measures, operations and procedures aimed for preventing and overcoming financial difficulties .The resolution tools, as regulated in Law no. 312/2015 on recovery and resolution of credit institutions and investment companies, as well as on amending and supplementing certain acts in the financial system, and applied by the National Romanian Bank , as a resolution authority, shall be use to defend financial stability and to protect the public interest.